The Root-Ely Modified Test of Rectus Femoris Spasticity Has Reliability in Individuals with Cerebral Palsy. Issue 2 (July 2018) - Drefus, Lisa C.; Clarke, Siobhan; Resnik, Karen; Koltsov, Jayme; Dodwell, Emily R.; Scher, David M.
Background: Stiff-knee gait is a common gait deviation in individuals with cerebral palsy (CP) due to rectus femoris (RF) muscle spasticity. The Duncan-Ely test is a velocity-dependent measurement of spasticity that is recorded as positive or negative. At our institution, we use a modification of the Duncan-Ely test, a 5-point ordinal rating scale, which delineates where the catch occurs within the rapid arc of knee flexion. It has been named the Root-Ely test. Questions/Purposes: We sought to determine the intra- and inter-rater reliability of the Duncan-Ely and Root-Ely tests in pediatric patients with CP. Methods: A convenience sample of 20 ambulatory subjects was recruited; mean age was 10.5 ± 4.5 years, and the Gross Motor Function Classification System (GMFCS) levels were I–III. Five clinicians measured each individual's RF spasticity using the Root-Ely protocol during a single visit. Simple κ statistics with 95% confidence intervals (CI) were utilized for intra-rater reliability and weighted κ statistics with 95% CI for inter-rater reliability. Results: The Root-Ely scale intra-rater reliability was 0.77 to 0.90 and inter-rater reliability was 0.32 to 0.87. Inter-rater reliability was good to excellent among experienced clinicians and fair to moderate in new clinicians. Conclusion: The Root-Ely 5-point scale has acceptable intra- and inter-rater reliability in pediatric individuals with CP among experienced clinicians. The Root-Ely test allows experienced clinicians to reliably quantify severity of RF spasticity and may give orthopaedic surgeons a clinical tool to better predict ideal candidates for RF transfers in individuals with CP in order to improve stiff-knee gait.